Simulating the Effect of Feed-In Tariff on Renewable Energy Penetration: A System Dynamics Approach - Salman, Ahmad; Razman, Mat Tahar; Cheng, Jack Kie (2014)
In Malaysia, solar photovoltaic (PV) has got the most beneficial feed-in tariff (FIT) rates as compared to other technologies. Managing continued investments and payments is a complex task for the government due to uncertainty, nonlinearity, and dynamics involved. The objective is to develop an assessment model which can evaluate the FIT scheme for solar PV system. The model is based upon system dynamics methodology to develop a simulation for assessing FIT policy. 2012–2050 is the time horizon used in simulations. We modelled the interconnection of FIT and other important variables in a feedback fashion. The interconnection in the system is between FIT rate, cumulative PV capacity, cumulative carbon emission avoided, and the amount of funds needed to support the scheme. The technological-economic interactions were modelled by the cost of PV system. Three scenarios corresponding to the highest (S1), average (S2), and a minimum (S3) FIT rates are analysed. A degression rate of 8 % annually in FIT is employed. In S1, with the highest FIT rate of 1.23 RM/kWh, 1148 MW capacity comes on line with expenditure of 5 billion RM. With an average FIT rate of 862 MW, 3.5 billion RM will be paid. Finally, in S3, with the least FIT rate of 0.85 RM/kWh, capacity will be 526 MW and total payment will be 1.7 billion RM for a 21-year period. CO2 emissions cost 0.036 RM/kg, 0.032 RM/kg, and 0.026 RM/kg for S1, S2, and S3, respectively, in 2050.